New Facts on Consumer Price Rigidity in the Euro Area - Cristina Conflitti; Riemer P. Faber; Brian Fabo; Ludmila Fadejeva; Erwan Gautier; Valentin Jouvanceau; Jan-Oliver Menz; Teresa Messner; Pavlos Petroulas; Pau Roldan-Blanco; Fabio Rumler; Sergio Santoro; et al. (Oesterreichische Nationalbank (OeNB), 2022)
Using CPI micro data for 11 euro area countries covering about 60% of the euro area consumption basket over the period 2010-2019, we document new ndings on consumer price rigidity in the euro area: (i) each month on average 12.3% of prices change, which compares with 19.3% in the United States; when we exclude price changes due to sales, however, the proportion of prices adjusted each month is 8.5% in the euro area versus 10% in the United States; (ii) differences in price rigidity are rather limited across euro area countries but much larger across sectors; (iii) the median price increase (resp. decrease) is 9.6% (13%) when including sales and 6.7% (8.7%) when excluding sales; cross-country heterogeneity is more pronounced for the size than for the frequency of price changes; (iv) the distribution of price changes is highly dispersed: 14% of price changes in absolute values are lower than 2% whereas 10% are above 20%; (v) the overall frequency of price changes does not change much with in ation and does not react much to aggregate shocks; (vi) changes in infation are mostly driven by movements in the overall size; when decomposing the overall size, changes in the share of price increases among all changes matter more than movements in the size of price increases or the size of price decreases. These ndings are consistent with the predictions of a menu cost model in a low in ation environment where idiosyncratic shocks are a more relevant driver of price adjustment than aggregate shocks.
Keywords: D40; E31; 330; price rigidity; in ation; consumer prices; micro data